PENGARUH KUALITAS PELAYANAN DAN KERAGAMAN PRODUK TERHADAP KEPUASAN PELANGGAN DI APOTEK INDRA DENPASAR - I Made Bayu Dwika Artawan; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The state of the pharmaceutical industry in Denpasar City is currently growing rapidly. Pharmacies with low competitiveness face tough challenges in the pharmaceutical industry. This is because the number of pharmacies that are established and close together makes conditions increasingly unfavorable for business development. With the rapid growth of the pharmaceutical industry, the owners and managers of these pharmaceutical businesses must rack their brains to increase competitiveness in order to survive. In improving business development, it is important for pharmacies to provide good pharmaceutical services for customers. This research was conducted with the aim of knowing the effect of service quality and product diversity on customer satisfaction at Apotek Indra Denpasar. The research population is customers who visit the Indra Denpasar Pharmacy. The sample in this study was 160 respondents who were determined based on the purposive sampling method. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that service quality and product diversity have a positive effect on customer satisfaction at Apotek Indra Denpasar.